Family Moral Education in Preparing for Life in an Islamic Society - Ira Suryani; Andre Frarera; Nanda Nurul Baiti; Siti Nurhaliza (Tarbiyah Departement collaboration with AMCA, 2023)
This study aims to provide an explanation and as a reference for families in preparing moral provisions for children before entering the wider community. It is not taboo that a pluralistic society can affect a person's behaviour, so family education plays a vital role in the educational process that is firmly entrenched so that children are not easily affected by negative things from the effects of society. The library method was used in this study. Data were obtained by taking notes and documentation from books, journals, the internet, and others. Data analysis using reduction, presentation and conclusion. The study results show that morals in the family can be grouped into morals towards parents, which include being kind to parents, obeying their advice, glorifying them wholeheartedly, and offering prayers for parents and others. Second, morals towards partners, including maintaining harmony between husband and wife, forming an ideal Islamic family, and being open to each other and others. Third, morals towards children, covering, fulfilling obligations as parents, teaching manners, and fulfilling children's rights. In life in the community, the behaviour will reflect how education in the family takes place. Therefore it is a crucial thing to pay attention to, especially parents.